Penambahan Ekstrak Kulit Buah Naga terhadap Derajat Warna, Kadar Antosianin, Aktivitas Antioksidan dan Sifat Sensoris Cendol - Ainul Hasanah; Nurrahman Nurrahman; Agus Suyatno (Universitas Muhammadiyah Semarang, 2022)
Cendol is a food product whose basic ingredients are rice flour, tapioca flour and other additives such as water and food coloring. Dragon fruit waste, namely the skin contains antioxidant compounds and anthocyanins which can be used as natural dyes in cendol. In making cendol with the addition of dragon fruit peel extract, it can be an alternative food product that is good for health. The bioactive components in dragon fruit peel are expected to increase the functional properties of cendol dragon fruit peel extract. This study aims to determine the effect of adding dragon fruit peel extract to the degree of color, anthocyanin levels, antioxidant activity and sensory properties of cendol. The steps taken were starting from making dragon fruit peel extract, making cendol dragon fruit peel extract and then analyzing the degree of color, anthocyanin levels, antioxidant activity and sensory properties of cendol. The research method was experimental using a monofactor completely randomized design (CRD) with the addition of dragon fruit peel extract using four treatments (0, 5, 10 and 15%) and six replications resulting in 24 experimental units. The results showed that there was an effect on the degree of color, anthocyanin levels, antioxidant activity and sensory cendol with the addition of dragon fruit peel extract 15% with a score of 2.82. As for the degree of color is 78.23, anthocyanin is 259.07 mg/L and antioxidant activity is 39.70% RSA.